PENGARUH VARIASI PUTARAN MESIN DAN PEMANASAN BAHAN BAKAR BENSIN MELALUI PIPA KAPILER BERSIRIP RADIAL DI DALAM UPPER TANK RADIATOR TERHADAP KONSUMSI BAHAN BAKAR BENSIN PADA MESIN TOYOTA KIJANG - Nurachman, Arif (Jurnal Nosel, 2013)
The result of this research shows that the effect the usage of heating gasoline fuel through a capillary tube which is radial finned in the upper tank radiator at engine speed 1000 r.p.m., 2000 r.p.m., and 3000 r.p.m.. Average consumption at engine speed 1000 r.p.m. normal Toyota Kijang average consumption 32,066×10-3 cc per cycle. With the use of heating fuel use 3 copper pipe with fins spaced 10 mm fuel consumption by 25,174×10-3 cc per cycle. Fuel consumption decreased by 6,892×10-3 cc per cycle or 21,58%. At engine speed 2000 r.p.m. normal Toyota Kijang average consumption 38,487×10-3 cc per cycle. With the use of heating fuel use 3 copper pipe with fins spaced 10 mm fuel consumption by 28,121×10-3 cc per cycle. Fuel consumption decreased by 10,366×10-3 cc per cycle or 26,93%. At engine speed 3000 r.p.m. normal Toyota Kijang average consumption 36,783×10-3 cc per cycle. With the use of heating fuel use 3 copper pipe with fins spaced 10 mm fuel consumption by 31,187×10-3 cc per cycle. Fuel consumption decreased by 5,596×10-3 per cycle or 15,21%. The conclusion of this research is the usage of fuel heating using three copper tubes with the range between the fins is 10 mm in the upper tank of radiator can reduce the biggest lowers fuel consumption on the Engine of Toyota Kijang 1989.